Phloem RNA-binding proteins as potential components of the long-distance RNA transport system - PALLAS, VICENTE; Gomez, Gustavo (Frontiers in Plant Science, 2013)
RNA-binding proteins (RBPs) govern a myriad of different essential processes in eukaryotic cells. Recent evidence reveals that apart from playing critical roles in RNA metabolism and RNA transport, RBPs perform a key function in plant adaption to various environmental conditions. Long distance RNA transport occurs in land plants through the phloem, a conducting tissue that integrates the wide range of signalling pathways required to regulate plant development and response to stress processes. The macromolecules in the phloem pathway vary greatly and include defence proteins, transcription factors, chaperones acting in long distance trafficking, and RNAs (mRNAs, siRNAs and miRNAs). How these RNA molecules translocate through the phloem is not well understood, but recent evidence indicates the presence of translocatable RNA-binding proteins in the phloem, which act as potential components of long distance RNA transport system. This review updates our knowledge on the characteristics and functions of RBPs present in the phloem.